2015
DOI: 10.1108/jfmpc-07-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Finance-based scheduling using meta-heuristics: discrete versus continuous optimization problems

Abstract: Purpose – The purpose of this paper is to compare the performance of the genetic algorithm (GA), simulate annealing (SA) and shuffled frog-leaping algorithm (SFLA) in solving discrete versus continuous-variable optimization problems of the finance-based scheduling. This involves the minimization of the project duration and consequently the time-related cost components of construction contractors including overheads, finance costs and delay penalties. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The proposed problem was named the financebased scheduling problem, in which the total project duration was minimized, and the finance-availability constraint was fulfilled in the meantime. To account for large-size projects, Ali and Elazouni [13] and Alghazi et al [14] applied genetic algorithms to develop finance-based schedule models, while Elazouni et al [15] and Al-Shihabi and AlDurgam [16] used simulated annealing and max-min ant system algorithms, respectively, to address the problem. Further research efforts were undertaken by Fathi and Afshar [17] and Elazouni and Abido [18] to consider multiple objectives in integrating a project's cash flow with its schedule, as well as by Liu and Wang [19] and El-Abbasy et al [20] to consider project finance in a multiproject scheduling context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed problem was named the financebased scheduling problem, in which the total project duration was minimized, and the finance-availability constraint was fulfilled in the meantime. To account for large-size projects, Ali and Elazouni [13] and Alghazi et al [14] applied genetic algorithms to develop finance-based schedule models, while Elazouni et al [15] and Al-Shihabi and AlDurgam [16] used simulated annealing and max-min ant system algorithms, respectively, to address the problem. Further research efforts were undertaken by Fathi and Afshar [17] and Elazouni and Abido [18] to consider multiple objectives in integrating a project's cash flow with its schedule, as well as by Liu and Wang [19] and El-Abbasy et al [20] to consider project finance in a multiproject scheduling context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They suggested that the inclusion of overlap tends to incur a higher amount of overdraft while shortening the project completion time and leading to greater cash flow uncertainty. Moreover, some researchers developed cash flow models based on algorithms (Badell et al, 2005;Metwally, 2005, 2007;Elazouni et al, 2015). For instance, Metwally (2005, 2007) used genetic algorithms to devise finance-based schedules to maximize project profit by minimizing financing costs and indirect costs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some researchers developed cash flow models based on algorithms (Badell et al. , 2005; Elazouni and Metwally, 2005, 2007; Elazouni et al. , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, contractors often overlook the importance of indirect expenses estimation due to its low percentage contribution to the contract sum (Chan, & Pasquire, 2002). Moreover, planning the optimal project completion is a major construction management aspect for building constructors towards maximising their profit margins and succeeding client's satisfaction through the expedient delivery of the final product for building owners to start reaping the anticipated benefits (Elazouni et al, 2015). Notwithstanding the significance of both indirect expenses' management and TCO on project success, to the author's knowledge, there is no research exploring the effect of indirect costs' variation on TCO and the resulting project profitability.…”
Section: Introductionmentioning
confidence: 99%